2022
DOI: 10.1098/rspb.2021.2338
|View full text |Cite
|
Sign up to set email alerts
|

Habitat mediates coevolved but not novel species interactions

Abstract: Ongoing recovery of native predators has the potential to alter species interactions, with community and ecosystem wide implications. We estimated the co-occurrence of three species of conservation and management interest from a multi-species citizen science camera trap survey. We demonstrate fundamental differences in novel and coevolved predator–prey interactions that are mediated by habitat. Specifically, we demonstrate that anthropogenic habitat modification had no influence on the expansion of the recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…Despite our strong caveats on the interpretation of modelled pine marten densities, our study reflects the results from field observations (Sheehy et al 2018, Twining et al 2020a that suggest that, at the level of pine marten density observed in the UK and Republic of Ireland, the impact of pine marten predation on red squirrel density is low. Note however, that recent evidence suggests that the impact of pine marten on red squirrel density in low resource conifer dominated habitats in Northern Ireland (where field voles are absent) may be high (Twining et al 2022).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite our strong caveats on the interpretation of modelled pine marten densities, our study reflects the results from field observations (Sheehy et al 2018, Twining et al 2020a that suggest that, at the level of pine marten density observed in the UK and Republic of Ireland, the impact of pine marten predation on red squirrel density is low. Note however, that recent evidence suggests that the impact of pine marten on red squirrel density in low resource conifer dominated habitats in Northern Ireland (where field voles are absent) may be high (Twining et al 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Those species exhibit irregular outbreaks in density linked to tree seed masting events (Pucek et al 1993), however they do not reach the densities exhibited by field voles in mainland UK (Smal and Fairley 1980). Thus, the impact of a temporal refuge may be more pronounced in Scotland and northern England than in Ireland, which may explain why the grey squirrel decline that has coincided with the recovery of pine marten in Ireland has been rapid (Sheehy and Lawton 2014, Twining et al 2020a, 2022). Note also that, while we considered the known influence of the proportion of coniferous and deciduous tree cover on squirrel species carrying capacity, we implicitly held the amount of field vole habitat constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has indicated that the recovery of native predators can benefit native prey species that compete with invasive prey in circumstances where predation is more pronounced on the naïve invasive species (Sheehy and Lawton, 2014;Twining et al, 2022b). Pine martens (Martes martes) are generalist semi-arboreal predators, native to Great Britain and Ireland, that have been reported to prey upon grey squirrels at a greater frequency compared to red squirrels (Twining et al, 2020c), which is believed to occur due to evolutionary naïvety and a lack of anti-predator behaviours in grey squirrels (Twining et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Recent legal protection has led to the on-going recovery of pine marten that has led to the recolonisation of much of their historical range in Scotland and Ireland. This recovery has resulted in landscape scale declines of established grey squirrel populations that has allowed the re-establishment of red squirrels in regions where they have previously been excluded (Sheehy and Lawton, 2014;Twining et al, 2022bTwining et al, , 2020cSheehy et al, 2018;Bamber et al, 2020). There remains a paucity of information on the impact of pine marten recovery on the prevalence of SQPV in squirrel populations (but see Roberts and Heesterbeek, 2021).…”
Section: Introductionmentioning
confidence: 99%